Management of Rotylenchulus reniformis in soybean cultivation positively impacts the yield of cotton grown in succession - Rosângela Aparecida Silva; Juliana Nunes Oliveira; Guilherme Lafourcade Asmus (Pesquisa Agropecuária Tropical)
The Rotylenchulus reniformis nematode efficiently multiplies in soybean roots, thereby increasing the inoculum in soils subsequently cultivated with cotton. This study aimed to evaluate the effect of using nematode-resistant soybean cultivars, combined with chemical, phytochemical or biological nematicides, on the soil population of the nematode, as well as the yield of cotton grown in succession to soybean. Two experiments were conducted in naturally infested areas, employing a factorial design (cultivars × nematicides). There was a reduction in the soil population density of R. reniformisdue to cultivating the nematode-resistant soybean variety, with positive repercussions on the yield of cotton grown in succession to soybean. No significant effects of chemical, phytochemical or biological nematicides were observed on R. reniformis or cotton yield following the cultivation of the nematode-resistant soybean.